Stanisław Staszic. Między Bogiem a naturą - Skodlarski, Janusz (Annales. Etyka w Życiu Gospodarczym, 2015)
From a very young age till the last days of his life, Stanisław Staszic was occupiedby the question of the relationship between God and Nature. In particular, the Polishthinker was interested in the vision of the world in which human life and Naturewere seen in unison, in accordance with laws of reason and the outcomes of scientificinvestigations. His deliberations on Nature validated his monistic worldview,encompassed within a deistic general framework. Staszic pointed out many timesthat natural order is the creation of God, however, earthly issues are in the hands ofhumans. In the last years of his life he withdrew from God. He did not accept theChurch’s hierarchy, while his approach to the Creator was ambivalent.